PENINGKATAN HASIL BELAJAR DAN AKTIVITAS SISWAMELALUI PENERAPAN MODEL BELAJAR BRUNERPADAPOKOK BAHASAN SEGITIGA KELAS VII SMPLB-B(TUNA RUNGU) YAYASAN TPA JEMBERSEMESTER GENAP TAHUNAJARAN 2012/2013 - Harry, Fajar; Susanto, S; Setiawan, Toto' Bara (Kadikma, 2014)
Abstract.The purpose of this research are 1) todetermine the application ofmathematical learningusinglearning theoryBruner. 2) to determine theactivity ofstudentsin theteachingandlearningprocessby usinglearningBrunerintriangletopic. Brunertheorystepsconsistof1) information, 2) transformation, 3) andevaluation. transformationhas3stages:enaktif, iconic, andsymbolic. targetedresearch in SMPLB-B Yayasan TPA Jember 2012/2013 academic year. The data collection method applied on this research are observatian, interview, test, and dokumentation. Data analysis that is used in this research are1) implementation of learningBruner, 2) the percentageof teachersandstudentsin teaching and learning. From the observation result, teaching and learning process pertained to the active criteria and increased from cycle 1 to cycle 2. From the final test in cycle 1, the value of classical completeness is 0% and the value of classical completeness in cycle 2 is 80%. The classical completness in cycle 2 increased compared with the first cycle. So, from these result it can be concluded that the application of Brunerlearningusinglearning theoryintriangulartopicscanincreasestudents'mathachievement. Key Words:Brunertheory,Lesson plan, student worksheet, student homework.